1974
DOI: 10.1111/j.1469-8137.1974.tb02142.x
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhizas in Plants Colonizing Coal Wastes in Scotland

Abstract: SUMMARYAll the grasses and nearly all the dicotyledonous plants growing on three coal tips in Scotland were infected by vesicular-arbuscular mycorrhizal fungi. Infection levels ranged from 20 to 90%. Three main types of fungal endophytes were identified, two being Endogone spp. and one with very narrow hyphae. Mixed infections were present in some plants and there was some evidence that the endophytes occurred in different areas of the tips. The ecological importance of the mycorrhizas in these habitats is dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

1978
1978
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(36 citation statements)
references
References 30 publications
0
34
0
2
Order By: Relevance
“…Trabalhos diversos relatam a participação decisiva e positiva dos fMA na fixação de dunas (Koske 1981, Koske & Polson 1984, na recomposição de vegetação de áreas sujeitas a secas (Allen & Boosalis 1983) ou submetidas a impactos ambientais diversos, tais como chuvas ácidas (Killham & Firestone 1983), depósito de metais pasados (Gildon & Tinker 1983a, 1983b, deslizamentos (Sylvia & WiIl1988), áreas de mineração (Daft & Nicolson 1974), entre outros O estudo de fMA sob vegetação nativa em áreas preservadas fornece dados sobre a biologia e a ecologia desses organismos em áreas de menor interferência antrópica, oferecendo subsídios para seu manejo em outras situações.…”
Section: Introductionunclassified
“…Trabalhos diversos relatam a participação decisiva e positiva dos fMA na fixação de dunas (Koske 1981, Koske & Polson 1984, na recomposição de vegetação de áreas sujeitas a secas (Allen & Boosalis 1983) ou submetidas a impactos ambientais diversos, tais como chuvas ácidas (Killham & Firestone 1983), depósito de metais pasados (Gildon & Tinker 1983a, 1983b, deslizamentos (Sylvia & WiIl1988), áreas de mineração (Daft & Nicolson 1974), entre outros O estudo de fMA sob vegetação nativa em áreas preservadas fornece dados sobre a biologia e a ecologia desses organismos em áreas de menor interferência antrópica, oferecendo subsídios para seu manejo em outras situações.…”
Section: Introductionunclassified
“…Appearance or absence of vesicles and arbuscules depends on the host; and the presence of arbuscules and absence of vesicles is not unusual for VA endophyte (Daft and Nicolson, 1974).…”
Section: Discussionmentioning
confidence: 98%
“…Without this symbiosis many plants fail to grow past the germination stage or show a decreased growth rate , Masse 1973. Many studies have shown that this relationship is fragile and can be easily disturbed (Bethlenfalvy and Dakessian 1984, Daft and Nicolson 1974. These studies show that as the severity of disturbance increases, i.e., from livestock grazing (Bethlenfalvy andDakessian 1984, Reece and to surface mining , there is a corresponding decrease in the frequency of V AM propagules and/ or colonization.…”
Section: Impact Of Fire On the Microbial Processes Inmentioning
confidence: 90%